Pengaruh Penguatan Pendidikan Karakter (PPK) terhadap Kedisiplinan dan Moralitas Siswa di SMPN 6 Pekanbaru - Khotib Raja Ritonga; Risnawati Risnawati; Fikri Hamdani (Journal on Education, 2025)
The rapid development of globalization has a major influence on social, cultural, and educational life throughout the world, including Indonesia. The purpose of this study is to, 1. Analyze the influence of strengthening character education (PPK) on the discipline of students of SMPN 6 Pekanbaru, 2. Analyze the influence of character education (PPK) on the morality of students of SMPN 6 Pekanbaru, 3. Analyze the influence of strengthening character education (PPK) on the discipline and morality of students of SMPN 6 Pekanbaru. The results of this study are, (1) there is an influence of Strengthening Character Education on Student Discipline as proven by the results of the first hypothesis test in this study showing a significance of the ANOVA table of 0.000 less than 0.05 which means Ho is rejected and Ha is accepted; (2) there is an influence between the variable Strengthening Character Education on Student Morality, as proven by the results of the second hypothesis test which shows a significance value of the ANOVA table of 0.000 less than 0.05 which means Ho is rejected and Ha is accepted; and (3) there is an influence between the variable Strengthening Character Education on Student Discipline and Morality. Proven by the results of multiple regression analysis showing a significant value of 0.000. Sig. in the ANOVA table 0.000 is less than 0.05, which means Ho is rejected and Ha is accepted.